Droughts and aridity in northeast Brazil - KUMAR, K.KARUNA; SILVA, JOSE ANTONIO TOMAS DA; SILVA, BERNAROO BARBOSA DA (MAUSAM, 1997)
ABSTRACT. Results of a study of droughts and aridity in northeast Brazil are presented in this paper. The study is based on the analysis of yearly water balances at fifteen stations in the region. Incidence of droughts of varying intensities at the stations is discussed. Climatic shifts at the stations are evaluated on the basis of the moisture index values. The use of the cumulative deviation technique in drought studies is briefly mentioned.